Employee discourse: tensions between the use of English and multilingual exchanges in daily work activities. - LEJOT, EVE (International Journal of Language, Translation and Intercultural Communication, 2016)
A number of European projects – ELAN (2006), Dylan (2006-2011), CELAN (2011-2013) – have confirmed the importance of multilingualism in the workplace. They provide evidence that a multilingual environment increases the diversity and the quality of projects, while monolingualism can mean a loss of markets. Since the ‘80s, English as a lingua franca (ELF) has been accepted as the international business language. Although English is not considered a threat to multilingualism (House, 2002, 2003), tensions exist between these two forms of communication: ELF and multilingualism. In this paper, I present an analysis of Airbus employee interviews using argument formulas (Anscombre, Ducrot, 1983). The initial analysis of what is said before and after the connector “but/pero/aber/mais” within interviews in four languages indicates tensions between the use of English and multilingual exchanges in daily work activities. The combination of “enunciation frames” (Charolles, 1997) and the role of personal pronouns (Benveniste, 1974) shows that the employees adapt their communication according to workplace structures: they tend to use English at an executive or a departmental level, while at team and face-to-face levels their communication benefits from multilingual skills.